Effects of weight-bearing activities on bone mineral content and density in children and adolescents: a meta-analysis - Behringer, M.; Gruetzner, S.; McCourt, M.; Mester, M. (Journal of Bone and Mineral Research, 2014)
Osteoporosis and associated fractures are a major health concern in Western industrialized nations. Exercise during growth is suggested to oppose the involutional bone loss later in life by increasing peak bone mass. The primary aim of the present meta-analysis was to provide a robust estimate of the effect of weight-bearing activities (WBAs) on bone mineral content (BMC) and areal bone mineral density (aBMD), during childhood and adolescence. To locate relevant studies up to June 2012, computerized searches of multiple bibliographic databases and hand searches of key journals and reference lists were performed. Results were extracted by two independent reviewers. The quality of the included trials was assessed via the Physiotherapy Evidence Database (PEDro) score. The study group effect was defined as the difference between the standardized mean change for the treatment and control groups divided by the pooled pretest SD. From 109 potentially relevant studies, only 27 met the inclusion criteria. The analyzed training programs were capable of significantly increasing BMC and aBMD during growth. However, the weighted overall effect sizes (ESs) for changes in BMC (ES 0.17; 95% confidence interval [CI], 0.05-0.29; p < 0.05) and aBMD (ES 0.26; 95% CI, 0.02-0.49) were small. Stepwise backward regression revealed that more than one-third of the observed variance (r(2) = 0.35) between subgroups of the BMC dataset could be explained by differences in the amount of habitual calcium intake per day (beta 0.54, p < 0.01) and the maturational stage (beta -0.28, p < 0.01) at baseline. No significant moderators were identified for aBMD, possibly due to the small number of trials investigating WBAs on aBMD. The results of this meta-analysis conclude that WBAs alongside high calcium intake provide a practical, relevant method to significantly improve BMC in prepubertal children, justifying the application of this exercise form as an osteoporosis prophylaxis in this stage of maturity.